Teaching information literacy- for the benefit of the future profession and lifelong learning? - du Toit, Madeleine; Rydberg, Helena; Dorthé, Lotti (Nordic Journal of Information Literacy in Higher Education, 2013)
<!--[if gte mso 9]> <![endif]--><!--[if gte mso 9]> <![endif]--> What opportunities do dental hygienists have to search for information in his or her daily professional life? Do dental technicians continue to update their skills after graduation? Do private dental practitioners have access to databases? Are graduating students experiencing that training in information literacy is relevant in their professional life? These questions gave birth to the idea to study if and in what ways dental hygienists, dental technicians and dentists are searching for information in their professional life, and which information resources they have access to. Through a study of this kind we were hoping to evaluate our work with teaching information literacy. We sent a survey to 164 students that had graduated from the Faculty of Odontology during the years 2005-2009, and got 97 responses. From the responses we have seen that the most frequently used resources were Google, books, colleagues and journals. A far larger percentage of those who work within the public sector and universities have access to a library than those within the private sector. We have observed differences between the three professional groups in terms of search patterns and choice of sources. 79 % of the respondents answered that they benefit from what they learned through the library's instruction and guidance in their work. Thus, the lack of time often determines how often, and where, the information searching is done. Many expressed that they have forgotten what they learned during their studies and comment that refreshing these skills would be beneficial. The results made us think about how we could adjust our teaching in order to prepare the students for their professional life, without cutting down on the regular teaching which the students need in order to manage their studies. How do we highlight the future usefulness of information literacy? The students who graduate from Malmo University will be a part of the surrounding society with which the library should interact. Do we inform students of the services the library can offer them as professionals? Disposition Round table discussion A 10 minute presentation of our study, then a 25 minute discussion in smaller groups based on the questions below and finally 5 minutes to summarize. Learning for school or learning for life? What is important to you - the education or the future professional life or both? In what way can we better prepare students for professional life? What services have we to offer professionals today? Should we offer them other services in addition to the ones we currently offer? Should we evaluate the education based on the perspective of "lifelong learning"? Is it relevant? <!--[if gte mso 9]> Normal 0 21 false false false SV X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]--><!--[if gte mso 9]> Normal 0 21 false false false SV X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]--><!--[if gte mso 9]> Normal 0 21 false false false SV X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->